Una visión ponderada de la legislación laboral: comentarios al régimen MYPE y a la propuesta de «Ley de la Nueva Empresa» - Sánchez Reyes, Christian (2012)
A weighted view of labor law: commentaries on the MSE regime and the proposal «Law of New Enterprise»The present article evaluates constitutional character of the regime of Micro and Small Enterprises (MSE) and the legislative proposal of «Law of New Enterprise» from the jurisprudence of the Constitutional Court. With this purpose it starts with analyzing own characters of the right to equality as a classical liberal right that is based on social rights as the right to work. Finally, the article seeks to dispel doubt of whether those regimes, MSE and the Law of New Enterprise, they obey to a policy of promotion of employment or rather they introduce a differentiated treatment without objective basis and therefore unconstitutional.